Mobilizing community health assets through intersectoral collaboration for social connection: Associations with social support and well-being in a nationwide population-based study in Catalonia - Pablo Galvez-Hernandez; Ketan Shankardass; Martine Puts; Ann Tourangeau; Luis Gonzalez-de Paz; Angelina Gonzalez-Viana; Carles Muntaner (PLoS ONE, 2025)
Background Limited social connection among older adults poses a global public health challenge, reducing sources of support and affecting health and well-being. National public health strategies that leverage local intersectoral collaboration between key sectors such as primary and social care, community organizations, and society, have been advocated, yet their impact remains underexplored. Objective This study examines the regional variability in the uptake of a public health strategy in Catalonia that mobilizes community health assets, such as social clubs and leisure activities, through intersectoral collaboration and its associations with social support and mental well-being in older adults. Methods We conducted a population-based cross-sectional study using the Catalan Health Survey (2017-2021) with 6011 adults aged ≥ 60 years across 31 Health Sectors. Survey data were linked with area-level uptake metrics, generated using data analytic techniques. Individuals were categorized into three uptake groups based on the number and territorial distribution of asset-based initiatives within their area of residence. Multilevel regressions tested associations with social support (OSSS-3) and mental well-being (SWEMWBS), controlling for individual, contextual, and temporal factors. Results Participants’ average age was 74.1 years ±  10.0 with 53.3% women. From 2017 to 2021, 2312 asset-based initiatives were registered across Health Sectors, ranging from 0 to 342 per sector. Residing in sectors with the highest uptake of initiatives (>15 initiatives per 10,000 population) was associated with higher social support (β = .34, p < .01) and mental well-being scores (β =  1.11, p < .01). Conclusion Residing in areas with greater health assets mobilized through intersectoral collaboration was associated with higher social support and well-being among older adults. This study represents one of the first national evaluations of an intersectoral strategy aimed at mitigating the mental health impacts of limited social networks. Future public health strategies should prioritize equitable access for inclusive benefits.